An overlooked source of skin dose perturbation: Commercial tattoo inks in radiotherapy - Hongjun Park; Beechui Koo; Jungwook Shin; Byoung Hyuck Kim; James J. Sohn (PLoS ONE, 2026)
Approximately one-third of US adults have tattoos, yet the dosimetric impact of intradermal tattoo pigments during radiation therapy remains uncharacterized. Commercial tattoo inks contain unregulated metallic impurities including chromium, lead, and nickel, raising concerns about dose perturbations in tattooed skin. This work quantifies radiation dose perturbations induced by high-atomic-number (Z) tattoo pigments under clinically relevant radiotherapy conditions. Monte Carlo simulations (TOPAS) modeled layered skin phantoms with a 0.3-mm intradermal tattoo layer embedded at 1.25–1.55 mm depth. Three commercial inks were evaluated: carbon-based (black) and metal-containing (Fe-rich brown, Al-containing orange) at pigment loadings of 5–100 vol% within the tattoo layer, to establish upper-bound effects. Electron (6, 18 MeV) and photon (6, 18 MV) beams were simulated with standard clinical geometry (1 × 1 cm² field, SSD = 100 cm). Photon irradiation produced pronounced, depth-localized dose enhancement, with peak dose enhancement factor (DEF) reaching 2.5 for brown ink at 18 MV, a 62% mean increase relative to non-tattooed skin driven by high-Z–mediated secondary electron production. Electron beams exhibited energy-dependent behavior: 6 MeV produced modest enhancement (peak DEF ~ 1.07), while 18 MeV unexpectedly generated dose deficits (DEF < 1.0) due to enhanced lateral scattering. Critically, all perturbations remained depth-confined without lateral propagation, preserving spatial dose uniformity across tattooed and non-tattooed regions. Tattoo pigments containing toxic metals create substantial localized dose enhancements under photon irradiation but minimal perturbations under electron therapy. These modality-dependent effects represent a previously unrecognized source of dose uncertainty in radiotherapy and warrant consideration in treatment planning for the growing population of tattooed patients.